Project Evaluation of Steroid Management by Community Network in Si Trakul Subdistrict, Khukhan District, Si Sa Ket Province - Dokphong, Deanchai (Journal of Health Science of Thailand, 2018)
This descriptive study was conducted to evaluate steroid management project run by a community network in Si Trakul subdistrict, Khukhan district, Si Sa Ket province, participated by village health volunteers, Ban Non health workers and Khukhan Hospital professional team. In its investigation, screening, diagnosis and treatment of steroid affected cases, focus was made on those with Cushing’s syndrome, and adrenal insufficiency. Data were collected in a proactive case finding, interview and observation based on aguideline developed by a team of experts. The study reported 137 suspected cases of steroid uptake. Of which 78 duly underwent screening and only 4 of them were referred to Khukhan hospital for further medical investigation. As a result, 2 Cushing’s syndrome cases, an adrenal insufficiency case and a case with both disorders were diagnosed by an internal medicine doctor.